Evolution of physical-chemical parameters, microbial diversity and VOC emissions of olive oil mill waste exposed to ambient conditions in open reservoirs. (September 2018) - Hernández, D.; Astudillo, C.A.; Fernández-Palacios, E.; Cataldo, F.; Tenreiro, C.; Gabriel, D.
Highlights: Physical-chemical & biological parameters of orujo (O) and alperujo (A) were studied. Environmental conditions correlated with changes on physical-chemical properties. O and A stored over time under uncontrolled ambient conditions produced odorous VOCs. Fatty acid methyl esters were precursors of odors from O and A wastes. Fungal and bacterial diversity increased, playing a role in waste degradation. Abstract: In the olive oil extraction process, 20% olive oil is obtained. About 80% corresponds to waste, mainly alperujo and orujo. When these residues are stored in open reservoirs for later stabilization or potential reuse, odorous Volatile Organic Compounds (VOCs) are generated as products of waste decomposition. In this work, these emissions were studied by means of TD-GC/MS in relation to the changes in the physical-chemical (ashes, moisture, total phenols, pH, proteins, fibers, oils, fats) and biological parameters (bacterial and fungal diversity in Illumina platform) of waste for 6 months. The dynamics of these parameters were statistically related to the evolution of environmental variables (temperature, relative humidity, precipitation) and their effects on the most relevant physical-chemical parameters in order to evaluate their incidence in odorant VOCs emissions over time. The results showed a progressive increase in the diversity of both fungi and bacteria that were related, mainly, to a progressive decrease in the concentration of fatty acid methyl esters and the concentration of alkenes in the emissions; and to an increase of odorous compounds, mainly aldehydes, ketones and carboxylic acids, which were responsible for the unpleasant odors of waste. No significant differences were observed between the evolution of orujo characteristics compared to those of alperujo.